IN MILITARY PERSONNEL PERFORMED AND NILATERAL SPINAL - EPIDURAL ANESTHESIA OPERATION AND POSTOPERATION I TREATMENT OF TROMBOEMBOLI ASORATNOGO COMPLEX PREVENTION - Rakhmankulov E.J. Ph.D; associate professor Mirrakhimova S.Sh. Ph.D; Professor Avakov V.E. Chakganov O'.A. (Western European Studies, 2025)
In modern medicine, especially in the early period after traumatology and orthopedic surgery, the old preventive measures of deep vein thrombosis of the legs, pulmonary artery thromboembolism (DPE) are still kept up-to-date. Vy mojete nachat deformatsiyu gonarthrosis and coxarthrosis, using a heterogeneous virus, entering the hip and knee, using components that can be used and capsules dlya togo, chtoby vy could use it independently [1]. Especially, the Covid-19 pandemic caused the pathological process of the hip and knee joints to accelerate after recovery from the disease in the military servicemen suffering from this disease. Currently, there are two views on arthrosis of the hip and knee joints in patients with Covid19; the first is the presence of microthrombi in the vessels that supply blood to the femoral head, and the second is associated with the flushing out of the tissue of corticosteroids given to patients as membrane stabilizers during the disease. Ortopedicheskiy ukhod za bolnymi, vyzvannymi osteoarthrozom, ekazyvaet effektivnaya stimuliyat, no mozhet vysvatnyy endoprotezlas, at the same time, it is possible to actively restore ili syndromy, vyzvannye physiologiey. [2]. Complete endoprosthetic surgery is considered to be a procedure performed in the absence of effective treatment
Keywords: Pulmonary artery; thromboembolism, deep venous thrombosis; unilateral spinal anesthesia